Perinatal outcomes of singleton live births after late moderate-to-severe ovarian hyperstimulation syndrome: A propensity score-matched study - Ran, Shiyu; Zu, Ruowen; Wu, Huan; Zheng, Wei; Yang, Chen; Yang, Shuheng; Ren, Bingnan; Zhang, Wen; Du, Jiangbo; Guan, Yichun (Frontiers in Endocrinology, 2022)
Objective To evaluate whether singleton live births achieved following in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) in women with late moderate-to-severe ovarian hyperstimulation syndrome (OHSS) is associated with adverse perinatal outcomes. Methods This was a single-center retrospective cohort study conducted from January 2016 to June 2021. A total of 4,012 IVF/ICSI-fresh embryo transfer cycles that achieved singleton live births were included. According to the diagnosis of OHSS, the cycles were divided into two groups: late moderate-to-severe OHSS (MS-OHSS) group (n = 114) and non-OHSS group (n = 3,898). Multiple baseline covariates were controlled by propensity score matching, yielding 114 late MS-OHSS singleton live births matched to 337 non-OHSS singleton live births. The primary outcome of the study was normal term infant. The secondary outcomes were perinatal complications, gestational age at birth, birth weight, and birth height. Result(s) Before propensity score matching, no significant difference in perinatal outcomes was identified between late MS-OHSS group and non-OHSS group. After matching maternal age, BMI, basal serum FSH level, basal serum AMH level, basal antral follicle count, type of stimulation protocol, day of embryo development for embryo transfer, number of embryo transfer, and number of oocytes retrieved, there was still no significant difference in obstetric outcomes and neonatal outcomes between the two groups. Conclusion(s) The findings demonstrate that the perinatal outcomes were similar between the two groups. However, because the sample size of patients with late MS-OHSS was limited in this study, further investigations are warranted using a larger sample size.